2021
DOI: 10.1021/acs.joc.1c01850
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Annulation between 2-Aminobenzyl Alcohols and Benzaldehydes in the Presence of DMSO: Regioselective Synthesis of Substituted Quinolines

Abstract: An unexpected annulation among 2-aminobenzyl alcohols, benzaldehydes, and DMSO to quinolines has been disclosed. For the reported annulation between 2-aminobenzyl alcohols and benzaldehydes, the change of the solvent from toluene to DMSO led to the change of the product from the diheteroatomic cyclic benzoxazines to monoheteroatomic cyclic quinolines. This annulation can be used to synthesize regioselectively different substituted quinolines by the choice of different 2-amino alcohols, aldehydes, and sulfoxide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…Oxidation is unarguably a fundamental transformation in synthetic chemistry and chemical industry, especially in accessing ubiquitous (hetero)­aromatic compounds . Despite endless attempts to improve the efficiency and practicality of this transformation, most of the traditional oxidation reactions heavily rely on transition-metal-catalyzed or promoted strategies or on the use of toxic reagents and harsh reaction conditions . From a sustainability point of view, the development of chemical processes that extend beyond the traditional oxidations is still highly desirable and remains a long-standing challenge in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidation is unarguably a fundamental transformation in synthetic chemistry and chemical industry, especially in accessing ubiquitous (hetero)­aromatic compounds . Despite endless attempts to improve the efficiency and practicality of this transformation, most of the traditional oxidation reactions heavily rely on transition-metal-catalyzed or promoted strategies or on the use of toxic reagents and harsh reaction conditions . From a sustainability point of view, the development of chemical processes that extend beyond the traditional oxidations is still highly desirable and remains a long-standing challenge in synthetic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“… 1 Despite endless attempts to improve the efficiency and practicality of this transformation, most of the traditional oxidation reactions heavily rely on transition-metal-catalyzed or promoted strategies or on the use of toxic reagents and harsh reaction conditions. 2 From a sustainability point of view, the development of chemical processes that extend beyond the traditional oxidations is still highly desirable and remains a long-standing challenge in synthetic chemistry. The use of enzymes as catalysts in oxidations is of great appeal because of their mild, efficient, benign, and highly selective nature.…”
Section: Introductionmentioning
confidence: 99%
“…3 ‐ (thiophen ‐ 2 ‐ yl)quinoline ( 3 f ) [17] . Following the general procedure A, the title product was obtained as a pale yellow liquid.…”
Section: Methodsmentioning
confidence: 99%
“…Yield: 42 %, (28 mg); 1 H NMR (500 MHz, Chloroform-d) δ 8.78 (d, J = 1.9 Hz, 1H), 8.07 (d, J = 8.3 Hz, 1H), 7.91 (s, 1H), 7.77 (d, J = 8.2 Hz, 1H), 7.65 (t, J = 7.7 Hz, 1H), 7.52 (t, J = 7.5 Hz, 1H), 2.80 (t, J = 7.7 Hz, 2H), 1.71 (d, J = 7.6 Hz, 2H), 1.26 (s, 14H), 0.88 (t, J = 6.9 Hz, 3H). ; 13 [17] Following the general procedure A, the title product was obtained as a white solid. Yield: 72 %, (39 mg); 1 H NMR (500 MHz, Chloroform-d) δ 9.04 (d, J = 2.…”
Section: -Decylquinoline (3 N)mentioning
confidence: 99%
“…Scientists have found that dimethyl sulfoxide (DMSO) is not only a commonly used solvent but also frequently serves as a versatile and commercially available reagent, so DMSO as a methyl reagent has great potential in organic synthesis and maybe could be applied to direct methylation of alkenes . Recently, the reactions between alkenes and DMSO have been reported a lot; these reactions could be mainly divided into the following categories: First, DMSO as a methyl donor participated in the difunctionalization of alkenes with nucleophiles .…”
Section: Introductionmentioning
confidence: 99%